Tirzepatide - a new drug with great potential in controlling glycemia and body weight - Stabrawa , Magdalena; Prusinowski , Filip; Sarata , Maria Teresa; Kutaj, Aleksandra; Savitskaya, Tatyana; Hatala, Ignacy; Savitski, Kiryl (Quality in Sport, 2026)
Introduction and Purpose: Type 2 diabetes mellitus (T2DM) and obesity are major global public health challenges associated with increased morbidity, mortality, and reduced quality of life. Despite multiple pharmacological therapies, achieving optimal glycemic control and sustained weight reduction remains difficult in many patients. Tirzepatide, a dual glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) receptor agonist, has emerged as a promising therapeutic option. The aim of this review is to evaluate the clinical efficacy, safety profile, mechanism of action, and therapeutic potential of tirzepatide in the management of T2DM and obesity. Methods: A narrative review of current literature, including randomized controlled trials, meta-analyses, and European Medicines Agency documentation, was conducted to assess metabolic effects, dosing strategies, adverse events, and long-term implications of tirzepatide therapy. Results: Clinical trials show significant reductions in glycated hemoglobin (HbA1c), exceeding 2 percentage points in patients with T2DM, and dose-dependent body weight reduction of up to approximately 20% of baseline weight in individuals with obesity. Comparative analyses indicate greater efficacy than selective GLP-1 receptor agonists and basal insulin for glycemic control and weight reduction. The most common adverse events are gastrointestinal and occur mainly during dose escalation. Long-term cardiovascular and renal outcomes remain under investigation. Conclusions: Tirzepatide represents an important advancement in incretin-based therapy, offering combined metabolic benefits that may modify current treatment algorithms for T2DM and obesity. Although evidence supports high efficacy and acceptable safety, further long-term studies are needed to determine its effects on disease progression, cardiovascular outcomes, and sustained weight management.